Conductive polymer composition and conductive polymer film
Patent Information
- Application Number
- JP2026094764
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-10-19
- Filing Date
- 2026-06-05
- Publication Date
- 2026-09-08
AI Technical Summary
【0019】 本発明の導電性高分子組成物を用いて作成した導電性高分子膜は、本発明で使用した導電性高分子、カーボン材料それぞれ単独で作成した導電性高分子膜よりも高い導電性を示すという従来に無い顕著な効果を奏する。このため、本発明の導電性高分子組成物は、固体電解コンデンサ等の性能を向上させることができる点で、産業上極めて有用である。
Smart Images

Figure 2026143618000001 
Figure 2026143618000002 
Figure 2026143618000003
Abstract
Description
[Technical Field]
[0001] This invention relates to conductive polymer compositions and conductive polymer films. [Background technology]
[0002] Conductive polymer materials have been developed by doping π-conjugated polymers, such as polyacetylene, polythiophene, polyaniline, or polypyrrole, with electron-accepting compounds as dopants. Their applications are being explored in areas such as antistatic agents, solid electrolytes for capacitors, conductive paints, electromagnetic shielding, electrochromic elements, electrode materials, thermoelectric conversion materials, transparent conductive films, chemical sensors, and actuators. Among these conductive polymer materials, polythiophene-based conductive polymer materials are particularly useful in practical applications due to their chemical stability.
[0003] Polythiophene-based conductive polymer materials include PEDOT / PSS aqueous dispersions obtained by polymerizing 3,4-ethylenedioxythiophene (EDOT) in an aqueous solution of polystyrene sulfonic acid (PSS) as a dopant, and so-called self-doped conductive polymers that have substituents (sulfo groups, sulfonate groups, etc.) in the polymer main chain, either directly or via spacers, that provide both water solubility and doping effects. Examples include sulfonated polyaniline and PEDOT-S (see, for example, Patent Documents 1 and 2).
[0004] In recent years, there has been active research into new applications such as transparent electrodes and low-ESR capacitors, and the market is demanding conductive polymers with even higher conductivity. [Prior art documents] [Patent Documents]
[0005] [Patent Document 1] Japanese Patent Publication No. 2015-63652 [Patent Document 2] Japanese Patent Publication No. 2015-147834 [Overview of the project] [Problems that the invention aims to solve]
[0006] Self-doped conductive polymers are expected to have applications in antistatic materials, solid electrolytes for capacitors, transparent electrodes, and the like. However, conventionally known self-doped conductive polymers have had difficulty achieving the high conductivity required for solid electrolytic capacitors and the like. If the conductivity of self-doped conductive polymers can be improved, it will be possible to further improve the performance of solid electrolytic capacitors and the like. The object of the present invention is to provide a self-doped conductive polymer composition that exhibits high conductivity. [Means for solving the problem]
[0007] The inventors of the present invention conducted extensive research to solve the above problems and, as a result, discovered that the above problems can be solved by using a conductive polymer composition containing a specific self-doped conductive polymer and a carbon material, thereby completing the present invention.
[0008] In other words, the present invention relates to the conductive polymer composition and conductive polymer film described below.
[0009] [1] A conductive polymer composition containing 0.001 to 10% by weight of polythiophene (A), which contains at least two structural units selected from the group consisting of structural units represented by the following general formula (1) and structural units represented by the following general formula (2), and 0.001 to 5% by weight of carbon material (B).
[0010] [ka]
[0011] [In the above general formulas (1) and (2), R 2 [where m represents a hydrogen atom, a methyl group, an ethyl group, a linear or branched alkyl group having 3 to 6 carbon atoms, or a fluorine atom; where m represents an integer from 1 to 10; and where n represents 0 or 1.] [2] The conductive polymer composition according to [1] above, wherein the carbon material (B) is at least one selected from the group consisting of carbon nanotubes, graphene, fullerene, carbon nanohorns, activated carbon, graphite, carbon nanofibers, carbon black, and porous carbon.
[0012] [3] The conductive polymer composition according to [1] above, wherein the carbon material (B) is at least one selected from the group consisting of single-walled carbon nanotubes, double-walled carbon nanotubes, and multi-walled carbon nanotubes.
[0013] [4] The conductive polymer composition according to [1], wherein the carbon material (B) is a single-walled carbon nanotube.
[0014] [5] The conductive polymer composition according to any one of [1] to [4] above, wherein the compositional ratio of the polythiophene (A) to the carbon material (B) is 0.001 to 50 parts by weight of the carbon material (B) relative to 1 part by weight of the polythiophene (A).
[0015] [6] A method for producing a conductive polymer film, which comprises applying the conductive polymer composition according to any one of [1] to [5] above onto a support, and then drying the composition.
[0016] [7] A conductive polymer film comprising polythiophene (A) containing at least one structural unit selected from the group consisting of a structural unit represented by the following general formula (1) and a structural unit represented by the following general formula (2), and a carbon material (B).
[0017]
Chemical Formula
[0018] [In the above general formulas (1) and (2), R 2 [where m represents a hydrogen atom, a methyl group, an ethyl group, a linear or branched alkyl group having 3 to 6 carbon atoms, or a fluorine atom; where m represents an integer from 1 to 10; and where n represents 0 or 1.] [8] The conductive polymer film according to [7] above, wherein the composition ratio of the polythiophene (A) and the carbon material (B) is 0.001 to 50 parts by weight of the carbon material (B) per 1 part by weight of the polythiophene (A). [Effects of the Invention]
[0019] The conductive polymer film prepared using the conductive polymer composition of the present invention exhibits a remarkable and unprecedented effect: it shows higher conductivity than conductive polymer films prepared using the conductive polymer or carbon material alone. Therefore, the conductive polymer composition of the present invention is extremely useful industrially because it can improve the performance of solid electrolytic capacitors and the like.
[0020] Furthermore, the conductive polymer composition of the present invention exhibits a unique effect in that it displays high conductivity behavior that differs from conventional conductive polymer compositions using known conductive polymers. [Modes for carrying out the invention]
[0021] The present invention will be described in detail below.
[0022] The present invention relates to a conductive polymer composition containing 0.001 to 10% by weight of polythiophene (A), which contains at least two structural units selected from the group consisting of structural units represented by the following general formula (1) and structural units represented by the following general formula (2), and 0.001 to 5% by weight of carbon material (B).
[0023] [ka]
[0024] [In general formulas (1) and (2), R 2 [where m represents a hydrogen atom, a methyl group, an ethyl group, a linear or branched alkyl group having 3 to 6 carbon atoms, or a fluorine atom; where m represents an integer from 1 to 10; and where n represents 0 or 1.] In the above general formulas (1) and (2), R 2 This represents a hydrogen atom, a methyl group, an ethyl group, a linear or branched alkyl group having 3 to 6 carbon atoms, or a fluorine atom.
[0025] The linear or branched alkyl group having 3 to 6 carbon atoms is not particularly limited, but examples include n-propyl group, isopropyl group, n-butyl group, isobutyl group, sec-butyl group, tert-butyl group, n-pentyl group, isopentyl group, neopentyl group, tert-pentyl group, cyclopentyl group, n-hexyl group, 2-ethylbutyl group, or cyclohexyl group.
[0026] The above R 2 Regarding this, in terms of film-forming properties, it is preferable that it be a hydrogen atom, a methyl group, an ethyl group, or a fluorine atom, and more preferably a hydrogen atom or a methyl group.
[0027] In the above general formulas (1) and (2), m represents an integer from 1 to 10, and in terms of film-forming properties, it is preferably an integer from 1 to 6, more preferably an integer from 1 to 4, and even more preferably 2 or 3.
[0028] In the above general formulas (1) and (2), n represents 0 or 1, and is preferably 1 in terms of excellent conductivity.
[0029] The structural unit represented by the above general formula (2) represents the doping state of the structural unit represented by the above general formula (1).
[0030] Dopants that induce an insulator-metal transition through doping are divided into acceptors and donors. The former enters the vicinity of the polymer chain of a conductive polymer through doping and steals π electrons from the conjugated system of the main chain. As a result, a positive charge (hole) is injected onto the main chain, and is therefore also called a p-type dopant. The latter, conversely, donates electrons to the conjugated system of the main chain, and these electrons move within the conjugated system of the main chain, and is therefore also called an n-type dopant.
[0031] In this invention, the dopant is a sulfo group or sulfonate group covalently bonded within the polymer molecule, and is a p-type dopant. Polymers that exhibit conductivity without the addition of external dopants in this manner are called self-doped polymers.
[0032] The polythiophene (A) of the present invention can be produced by polymerizing a thiophene monomer represented by the following general formula (3) in water or an alcohol solvent in the presence of an oxidizing agent, and then, if necessary, by acid treatment.
[0033] [ka]
[0034] [In the above general formula (3), M represents a hydrogen ion or a metal ion. R 2 [where m represents a hydrogen atom, a methyl group, an ethyl group, a linear or branched alkyl group having 3 to 6 carbon atoms, or a fluorine atom; where m represents an integer from 1 to 10; and where n represents 0 or 1.] The metal ion represented by M in general formula (3) is not particularly limited, but examples include transition metal ions, noble metal ions, non-ferrous metal ions, alkali metal ions (e.g., Li ions, Na ions, and K ions), or alkaline earth metal ions.
[0035] R in general formula (3) 2 The definitions and preferred ranges of , m, and n are as follows: R in general formulas (1) and (2), respectively. 2The definitions and preferred ranges of m and n are the same as above.
[0036] The thiophene monomer represented by the above general formula (3) is not particularly limited, but specifically includes 6-(2,3-dihydro-thieno[3,4-b][1,4]dioxin-2-yl)hexane-1-sulfonic acid, 6-(2,3-dihydro-thieno[3,4-b][1,4]dioxin-2-yl)hexane-1-sulfonate sodium, 6-(2,3-dihydro-thieno[3,4-b][1,4]dioxin-2-yl)hexane-1-sulfonate lithium, 6-(2,3-dihydro-thieno[3,4-b][1,4]dioxin-2-yl ) Potassium hexane-1-sulfonate, 8-(2,3-dihydrothieno[3,4-b][1,4]dioxin-2-yl)octan-1-sulfonic acid, 8-(2,3-dihydrothieno[3,4-b][1,4]dioxin-2-yl)octan-1-sulfonate sodium, 8-(2,3-dihydrothieno[3,4-b][1,4]dioxin-2-yl)octan-1-sulfonate potassium, 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-propanesulfonate sodium, 3-[(2 ,3-Dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-propanesulfonate potassium, 3-[(2,3-Dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-methyl-1-propanesulfonate sodium, 3-[(2,3-Dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-ethyl-1-propanesulfonate sodium, 3-[(2,3-Dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-propyl-1- Sodium propanesulfonate, 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-butyl-1-propanesulfonate sodium, 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-pentyl-1-propanesulfonate sodium, 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-hexyl-1-propanesulfonate sodium, 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-isopropyl-1-propanesulfonate sodium, 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-isobutyl-1-propanesulfonate sodium, 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-isopentyl-1-propanesulfonate sodium, 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]- 1-Fluoro-1-propanesulfonate sodium, 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-methyl-1-propanesulfonate potassium, 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-methyl-1-propanesulfonic acid, 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-methyl-1-propanesulfonate ammonium, 3-[(2,3-di Hydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-methyl-1-propanesulfonate triethylammonium, 4-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-butanesulfonate sodium, 4-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-butanesulfonate potassium, 4-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]- Examples include sodium 1-methyl-1-butanesulfonate, potassium 4-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-methyl-1-butanesulfonate, potassium 4-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-fluoro-1-butanesulfonate, or potassium 4-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-fluoro-1-butanesulfonate, etc.
[0037] When the polymer obtained after polymerization of the thiophene monomer represented by general formula (3) is a salt of a metal ion (i.e., M is a metal ion), the obtained polymer can be treated with acid (for example, by ion exchange with a cation exchange resin) to convert M to a hydrogen ion. In other words, even if M in general formula (3) is a metal ion, it is possible to produce polythiophene (A) containing at least one structural unit selected from the group consisting of the structural unit represented by general formula (1) and the structural unit represented by general formula (2).
[0038] The conductive polymer composition of the present invention may further contain a compound (C) capable of forming an ion pair with the sulfonic acid group of polythiophene (A), which comprises at least two structural units selected from the group consisting of the structural unit represented by the general formula (1) and the structural unit represented by the general formula (2), in terms of excellent conductivity and coating properties. The compound (C) capable of forming an ion pair with the sulfonic acid group is not particularly limited, but examples include alkali metal compounds, ammonia, organic amine compounds, and quaternary ammonium salts. These compounds (C) react with the sulfonic acid group of polythiophene (A) to form an alkali metal ion salt, an ammonium ion salt, an organic ammonium ion salt, and a quaternary ammonium ion salt of polythiophene (A), respectively.
[0039] The aforementioned alkali metal compounds are not particularly limited, but examples include alkali metal salt compounds (e.g., lithium chloride, potassium chloride, sodium chloride, rubidium chloride, cesium chloride, lithium bromide, potassium bromide, sodium bromide, rubidium bromide, cesium bromide, etc.) or alkali metal hydroxides (e.g., lithium hydroxide, potassium hydroxide, sodium hydroxide, rubidium hydroxide, cesium hydroxide, etc.).
[0040] By incorporating the aforementioned alkali metal compound into the conductive polymer composition of the present invention, an alkali metal ion salt of the polythiophene (A) can be prepared. In this case, the polythiophene (A) is a polythiophene containing at least one structural unit selected from the group consisting of structural units represented by general formula (1') and general formula (2'), where M is an alkali metal ion. The alkali metal ion is not particularly limited, but examples include lithium ions, potassium ions, sodium ions, rubidium ions, or cesium ions.
[0041] The aforementioned organic amine compounds are not particularly limited, but examples include primary, secondary, or tertiary amine compounds with a total of 1 to 30 carbon atoms. More specifically, examples include methylamine, dimethylamine, trimethylamine, ethylamine, triethylamine, n-propylamine, isopropylamine, n-butylamine, isobutylamine, diisobutylamine, triisobutylamine, hexylamine, dihexylamine, trihexylamine, dioctylamine, trioctylamine, (2-ethylhexyl)amine, bis(2-ethylhexyl)amine Examples include amine, tris(2-ethylhexyl)amine, aminoethanol, dimethylaminoethanol, methylaminoethanol, diethanolamine, N-methyldiethanolamine, triethanolamine, 3-amino-1,2-propanediol, 3-methylamino-1,2-propanediol, 3-dimethylamino-1,2-propanediol, 1,4-butanediamine, triisobutylamine, triisopentylamine, triisooctylamine, imidazole, N-methylimidazole, 1,2-dimethylimidazole, pyridine, picoline, or lutidine.
[0042] By incorporating the aforementioned organic amine compound into the conductive polymer composition of the present invention, the organic amine compound reacts with the aforementioned polythiophene (A) to form an organic ammonium ion, thereby preparing an organic ammonium ion salt of the aforementioned polythiophene (A). At this time, the aforementioned polythiophene (A) is a polythiophene containing at least one structural unit selected from the group consisting of structural units represented by general formula (1') and general formula (2'), where M is an organic ammonium ion. The aforementioned organic ammonium ions are not particularly limited, but examples include primary, secondary, or tertiary ammonium ions with a total number of carbon atoms of 1 to 30. More specifically, examples include methylammonium, dimethylammonium, trimethylammonium, ethylammonium, triethylammonium, n-propylammonium, isopropylammonium, n-butylammonium, isobutylammonium, diisobutylammonium, triisobutylammonium, hexylammonium, dihexylammonium, trihexylammonium, dioctylammonium, trioctylammonium, (2-ethylhexyl)ammonium, bis(2-ethylhexyl)ammonium, tris(2-ethylhexyl)ammonium, 2-hydroxyethylammonium, Examples include N,N-dimethyl-N-(2-hydroxyethyl)ammonium, N-methyl-N-(2-hydroxyethyl)ammonium, di(2-hydroxyethyl)ammonium, N-methyl-N,N-di(2-hydroxyethyl)ammonium, N,N,N-tri(2-hydroxyethyl)ammonium, 2,3-dihydroxypropylammonium, N-methyl-N-(2,3-dihydroxypropyl)ammonium, N,N-dimethyl-N-(2,3-dihydroxypropyl)ammonium, 1,4-butanediammonium, triisobutylammonium, triisopentylammonium, triisooctylammonium, imidazole cation, N-methylimidazole cation, 1,2-dimethylimidazole cation, pyridinium ion, picolinium ion, or rutidinium ion.
[0043] The aforementioned quaternary ammonium compounds are not particularly limited, but examples include tetramethylammonium chloride, tetraethylammonium chloride, tetran-propylammonium chloride, tetran-butylammonium chloride, or tetran-hexylammonium chloride.
[0044] By incorporating the aforementioned quaternary ammonium compound into the conductive polymer composition of the present invention, the quaternary ammonium compound reacts with the aforementioned polythiophene (A) to form a quaternary ammonium ion, and a quaternary ammonium ion salt of the aforementioned polythiophene (A) is prepared. At this time, the aforementioned polythiophene (A) is a polythiophene containing at least one structural unit selected from the group consisting of structural units represented by general formula (1') and general formula (2') described later, wherein M is a quaternary ammonium ion. The quaternary ammonium ion is not particularly limited, but examples include tetramethylammonium ion, tetraethylammonium ion, tetran-propylammonium ion, tetran-butylammonium ion, or tetran-hexylammonium ion.
[0045] In the conductive polymer composition of the present invention, the content of compound (C) described above is preferably 0.001 to 20% by weight, more preferably 0.001 to 15% by weight, and even more preferably 0.003 to 10% by weight, in terms of having excellent surface resistance (low resistance).
[0046] When the conductive polymer composition of the present invention contains the above-mentioned compound (C), a polythiophene (A) containing at least one structural unit selected from the group consisting of the structural unit represented by general formula (1) and the structural unit represented by general formula (2) may be described as a polythiophene (A) containing at least one structural unit selected from the group consisting of the structural unit represented by the following general formula (1') and the structural unit represented by general formula (2').
[0047]
Chem.
[0048] [In the above general formula (1') and general formula (2'), R 2 represents a hydrogen atom, a methyl group, an ethyl group, a linear or branched alkyl group having 3 to 6 carbon atoms, or a fluorine atom; m represents an integer of 1 to 10; n represents 0 or 1; and M represents a hydrogen ion, an alkali metal ion, an ammonium ion, an organic ammonium ion, or a quaternary ammonium ion.]] In the above general formula (1') and general formula (2'), R 2 , m and n have the same definitions and preferred ranges as R 2 , m and n described in the above general formula (1) and general formula (2).
[0049] The alkali metal ion, ammonium ion, organic ammonium ion and quaternary ammonium ion in the above M are as described above. In the polythiophene (A) comprising at least one structural unit selected from the group consisting of the structural unit represented by the above general formula (1') and the structural unit represented by the general formula (2'), M does not need to be a single type, and multiple types can coexist.
[0050] The conductive polymer composition of the present invention is excellent in surface resistance value (low resistance), and the pH thereof is preferably in the range of 1.0 to 10.0, more preferably in the range of 1.5 to 8.0, and still more preferably in the range of 1.5 to 7.5. The pH can be controlled by the type and content of the compound (C) described above.
[0051] A polythiophene containing at least one structural unit selected from the group consisting of structural units represented by general formula (1') and structural units represented by general formula (2') can be produced by mixing a polythiophene (A) containing at least one structural unit selected from the group consisting of structural units represented by general formula (1) and structural units represented by general formula (2) with a compound (C) capable of forming an ion pair with the sulfonic acid group of polythiophene (A) (for example, the alkali metal compound, ammonia, amine compound, or quaternary ammonium compound mentioned above).
[0052] In the present invention, the conductivity of polythiophene (A) is not particularly limited, but it is preferably 10 S / cm or more, more preferably 50 S / cm or more, and even more preferably 100 S / cm or more as the conductivity (electrical conductivity) in the film state.
[0053] Furthermore, the polythiophene (A) used in this invention may be one synthesized based on prior art.
[0054] The conductive polymer composition of the present invention is characterized in that the concentration of polythiophene (A), which contains at least one structural unit selected from the group consisting of the structural unit represented by general formula (1) and the structural unit represented by general formula (2), is in the range of 0.001 to 10% by weight. In terms of excellent conductivity and operability, the concentration of polythiophene (A) in the conductive polymer composition of the present invention is preferably in the range of 0.03 to 7% by weight, and more preferably in the range of 0.05 to 5% by weight.
[0055] The conductive polymer composition of the present invention is characterized by containing a carbon material (B) with a concentration of 0.001 to 5% by weight. This characteristic makes it possible to obtain a coating film with high conductivity. The content of the carbon material (B) is preferably 0.003 to 2% by weight, and more preferably 0.005 to 1% by weight, in terms of high compatibility with the polythiophene (A) and maintenance of high conductivity.
[0056] The carbon material (B) is not particularly limited, but specifically, at least one selected from the group consisting of carbon nanotubes, graphene, fullerene, carbon nanohorns, activated carbon, graphite, carbon nanofibers, carbon black, and porous carbon is preferred, and carbon nanotubes are more preferred from the viewpoint of the conductivity of the resulting conductive polymer film.
[0057] The carbon nanotubes mentioned above are not particularly limited, but specifically, at least one selected from the group consisting of single-walled carbon nanotubes, double-walled carbon nanotubes, and multi-walled carbon nanotubes is preferred, and single-walled carbon nanotubes are more preferred from the viewpoint of the conductivity of the resulting conductive polymer film.
[0058] The diameter of the single-walled carbon nanotube is not particularly limited, but may be, for example, 20 nm or less, preferably 10 nm or less, and more preferably 5 nm or less. The lower limit of the diameter of the single-walled carbon nanotube is not particularly limited, but may be, for example, 0.4 nm or more, or 0.5 nm.
[0059] The carbon blacks mentioned above are not limited to any specific type, but examples include Ketjenblack or acetylene black.
[0060] Of the carbon materials (B) mentioned above, carbon nanotubes are preferred because they have high compatibility with the polythiophene (A) and can maintain high conductivity. More preferably, carbon nanotubes are at least one selected from the group consisting of single-walled carbon nanotubes, double-walled carbon nanotubes, and multi-walled carbon nanotubes, and single-walled carbon nanotubes are even more preferred.
[0061] Such carbon material (B) can be a commercially available product used as is, or it can be a carbon material prepared by a known method. It should be noted that carbon material (B) is often commercially available as an aqueous dispersant from the viewpoint of stability, etc. The composition of the present invention can be prepared using the aqueous dispersant of carbon material (B) as is, or it can be prepared using the aqueous dispersant of carbon material (B) that has been separately desolvent-removed and purified.
[0062] With respect to the conductive polymer composition of the present invention, from the viewpoint of the conductivity of the resulting conductive polymer film, the composition ratio of polythiophene (A) to carbon material (B) is preferably 0.001 to 50 parts by weight, more preferably 0.005 to 30 parts by weight, more preferably 0.01 to 20 parts by weight, and more preferably 0.01 to 15 parts by weight of carbon material (B) per 1 part by weight of polythiophene (A).
[0063] The conductive polymer composition of the present invention is not particularly limited, but may contain one or more solvents (D) selected from the group consisting of organic solvents and water, and it is preferable that it contains one or more solvents (D) selected from the group consisting of organic solvents and water.
[0064] The solvent (D) may consist of a solution of polythiophene (A) containing at least one structural unit selected from the group consisting of the structural unit represented by the general formula (1) and the structural unit represented by the general formula (2), or a solvent (D) accompanying the carbon material (B), or a solvent (D) may be added separately and included in the conductive polymer composition of the present invention.
[0065] The aforementioned water is not particularly limited, but examples include purified water, distilled water, ion-exchanged water, and pure water. It is preferable to use water of the highest possible purity for the added water.
[0066] The aforementioned organic solvents are not particularly limited, but examples include alcohols, ketones, ethers, aromatic compounds, and more specifically, methanol, ethanol, propanol, butanol, methoxyethanol, ethoxyethanol, butoxyethanol, ethylene glycol, propylene glycol monomethyl ether, propylene glycol monoethyl ether, methyl ethyl ketone, methyl isobutyl ketone, 2-pyrrolidone, N-methylpyrrolidone, dioxane, toluene, xylene, or chlorobenzene.
[0067] The concentration (content) of solvent (D) in the conductive polymer composition of the present invention is not particularly limited, but in terms of excellent workability, it is preferably in the range of 85 to 99.9% by weight, more preferably 90 to 99.9% by weight, and even more preferably 95 to 99.8% by weight.
[0068] The conductive polymer composition of the present invention may also contain additives (E) other than those listed above.
[0069] Other additives (E) mentioned above are not limited to those listed above, but examples include binders or surfactants. Additives (E) may be used individually or in combination with others.
[0070] The aforementioned binder is not particularly limited, but for example, water-soluble resins are preferred, and more specifically, examples include polyvinyl alcohol, polyvinylpyrrolidone, cellulose, water-soluble polyester resin compounds, water-soluble polyurethane resin compounds, or a mixture of a polyhydric alcohol and an organic acid having two or more carboxyl groups.
[0071] Examples of the aforementioned water-soluble polyester resin compounds include polyethylene terephthalate and polytrimethylene terephthalate. The water-soluble polyester resin compound may be of the self-emulsifying type or of the reinforced emulsion type, but a self-emulsifying water-soluble polyester resin compound is preferred from the viewpoint of water resistance and solvent resistance.
[0072] Examples of the aforementioned water-soluble polyester resin compounds that are readily available commercially include, for example, Byronal® (trade name), manufactured by Toyobo Co., Ltd., Pesresin (trade name), Pluscoat® (trade name), manufactured by Go-O Chemical Co., Ltd., Aronmelt® (trade name), manufactured by Toagosei Co., Ltd., Pesresin A (trade name), and Watersol® (trade name), manufactured by DIC Corporation.
[0073] The aforementioned water-soluble polyester resin compounds can be used individually or in combination of two or more types.
[0074] The aforementioned water-soluble polyurethane resin compound is mainly used in industrial applications as a urethane resin emulsion. It may be a self-emulsifying type or a reinforced emulsion type, but a self-emulsifying water-soluble polyurethane resin compound is preferred from the viewpoint of water resistance and solvent resistance. Examples of self-emulsifying types include anionic, cationic, and nonionic types, and any of these may be used. Furthermore, the water-soluble polyurethane resin compound is not particularly limited, but examples include polyether type, polyester type, and polycarbonate type.
[0075] Water-soluble polyurethane resin compounds are readily available commercially, such as those manufactured by Sanyo Chemical Industries, Ltd., with product names U-Coat (registered trademark), Permarin (registered trademark), and Euprene (registered trademark); those manufactured by Kusumoto Chemicals Co., Ltd., with product name NeoRez; those manufactured by ADEKA Corporation, with product name Adekabon Titer (registered trademark); those manufactured by Meisei Chemical Industry Co., Ltd., with product name Pascol (registered trademark); and those manufactured by DIC Corporation, with product name Hydran (registered trademark).
[0076] The aforementioned water-soluble polyurethane resin compounds can be used individually or in combination of two or more types.
[0077] The aforementioned polyhydric alcohols are not limited to any particular type, but examples include erythritol and pentaerythritol.
[0078] The organic acids having two or more carboxyl groups are not particularly limited, but examples include adipic acid and phthalic acid.
[0079] The aforementioned surfactant is not particularly limited, but for example, anionic surfactants, cationic surfactants, nonionic surfactants, amphoteric surfactants, fluorinated surfactants, or silicone-based surfactants can be used, but more preferably it is at least one selected from the group consisting of nonionic surfactants and amphoteric surfactants.
[0080] The aforementioned anionic surfactants are not particularly limited, but examples include sodium lauryl alcohol sulfate and sodium dodecylbenzenesulfonate.
[0081] The cationic surfactant mentioned above is not particularly limited, but commercially available products can be used, or generally known products can be manufactured separately and used.
[0082] The aforementioned nonionic surfactants are not particularly limited, but examples include polyethylene glycol-type surfactants, acetylene glycol-type surfactants, polyhydric alcohol-type surfactants, and polymer-type nonionic surfactants.
[0083] The polyethylene glycol-type surfactants mentioned above are not particularly limited, but examples include higher alcohol ethylene oxide adducts, alkylphenol ethylene oxide adducts, fatty acid ethylene oxide adducts, polyhydric alcohol fatty acid ester ethylene oxide adducts, higher alkylamine ethylene oxide adducts, oil and fat ethylene oxide adducts, or polypropylene glycol ethylene oxide adducts.
[0084] The aforementioned acetylene glycol-type surfactants are not particularly limited, but examples include 2,4,7,9-tetramethyl-5-decine-4,7-diol, Surfinol (manufactured by Air Products Inc., registered trademark), and Olfin (manufactured by Nisshin Chemical Industry Co., Ltd., registered trademark).
[0085] The aforementioned polyhydric alcohol-type surfactants are not particularly limited, but examples include fatty acid esters of glycerol, fatty acid esters of pentaerythritol, fatty acid esters of sorbitol and sorbitan, fatty acid esters of sucrose, alkyl ethers of high alcohols, and fatty acid amides of alkanolamines.
[0086] The amphoteric surfactants mentioned above are not particularly limited, but examples include betaine-type amphoteric surfactants. Examples of betaine-type amphoteric surfactants are not particularly limited, but examples include alkyldimethyl betaine, lauryldimethyl betaine, stearyldimethyl betaine, lauryldihydroxyethyl betaine, etc.
[0087] The aforementioned fluorine-based surfactant is not particularly limited as long as it has a perfluoroalkyl group, but examples include Pluscoat® RY-2, perfluoroalkanes, perfluoroalkyl carboxylic acids, perfluoroalkyl sulfonic acids, or perfluoroalkyl ethylene oxide adducts.
[0088] The aforementioned silicone-based surfactants are not particularly limited, but examples include polyether-modified polydimethylsiloxane, polyether ester-modified polydimethylsiloxane, hydroxyl group-containing polyether-modified polydimethylsiloxane, acrylic group-containing polyether-modified polydimethylsiloxane, acrylic group-containing polyester-modified polydimethylsiloxane, perfluoropolyether-modified polydimethylsiloxane, perfluoropolyester-modified polydimethylsiloxane, or silicone-modified acrylic compounds.
[0089] Furthermore, fluorine-based surfactants and silicone-based surfactants are effective as leveling agents in improving the flatness of coating films.
[0090] The conductive polymer composition of the present invention is characterized in that the content of the aforementioned additive (E) is 0.001 to 20% by weight, but is preferably 0.01 to 15% by weight, and more preferably 0.1 to 10% by weight, in terms of excellent handling properties.
[0091] The method for preparing the conductive polymer composition of the present invention is not particularly limited, but for example, it is a method of mixing a solution or solid of the polythiophene (A) with a solvent dispersion of the carbon material (B). At this time, the compound (C), the solvent (D), and / or the additive (E) may be added and mixed as needed. It is preferable to add and dissolve each material in water before mixing, but there is no particular limitation on the order in which the materials are added and mixed, and the conductive polymer composition of the present invention can be prepared by mixing these materials in any order.
[0092] The mixing temperature is not particularly limited, but can be anywhere from room temperature to under heating. A temperature between 0°C and 100°C is preferred.
[0093] The atmosphere during mixing is not particularly limited, but it can be in the air or in an inert gas.
[0094] Furthermore, in addition to general mixing and dissolution operations using stirrer tips or stirring blades, ultrasonic irradiation and homogenization (for example, using a mechanical homogenizer, ultrasonic homogenizer, or high-pressure homogenizer) may be performed during mixing. When homogenizing, it is preferable to do so while keeping the mixture cool to prevent thermal degradation of the polymer.
[0095] The viscosity (at 20°C) of the conductive polymer composition of the present invention is preferably 200 mPa·s or less, more preferably 100 mPa·s or less, and even more preferably 50 mPa·s or less.
[0096] The concentration of each component in the conductive polymer composition of the present invention may be adjusted by the blending ratio, or by concentration or dilution after blending. The concentration method may be by distilling off the solvent under reduced pressure, or by using an ultrafiltration membrane.
[0097] In the conductive polymer composition of the present invention, the concentration of all components other than water is preferably in the range of 0.1 to 20% by weight, more preferably in the range of 0.3 to 15% by weight, and even more preferably in the range of 0.5 to 10% by weight.
[0098] By using the conductive polymer composition of the present invention, it is possible to produce a conductive polymer film with high conductivity and / or exhibiting an electromagnetic wave shielding effect.
[0099] The method for forming a conductive polymer film from the conductive polymer composition of the present invention is not particularly limited, but for example, one method is to apply the conductive polymer composition of the present invention to a support and then dry it.
[0100] The support material is not particularly limited as long as it can be coated with the conductive polymer composition of the present invention, but examples include polymer substrates and inorganic substrates. Examples of polymer substrates include thermoplastic resins, nonwoven fabrics, paper, and resist film substrates. Examples of thermoplastic resins include polyethylene, polypropylene, polyethylene terephthalate, polyacrylate, or polycarbonate. Examples of nonwoven fabrics include those made of natural fibers or synthetic fibers. Examples of paper include those mainly composed of cellulose. Examples of inorganic substrates include glass, glass fibers, ceramics, aluminum oxide, or tantalum oxide.
[0101] Examples of methods for applying conductive polymer compositions include casting, dipping, bar coating, dispenser coating, roll coating, gravure coating, flexographic printing, screen printing, or offset printing.
[0102] The drying temperature of the coating film is not particularly limited as long as it is below the temperature at which a uniform conductive polymer film can be obtained and below the heat resistance temperature of the substrate, but it is preferably in the range of room temperature to 300°C, more preferably in the range of room temperature to 250°C, and even more preferably in the range of room temperature to 200°C.
[0103] The dry atmosphere may be air, an inert gas, a vacuum, or reduced pressure. From the viewpoint of suppressing the degradation of the conductive polymer film, an inert gas such as nitrogen or argon is preferred.
[0104] The thickness of the resulting conductive polymer film is not particularly limited, but 10 -3 ~10 3 A range of μm is preferred. More preferably 10 -3 ~10 2 It is μm.
[0105] The conductive polymer film obtained from the conductive polymer composition of the present invention exhibits excellent conductivity.
[0106] Furthermore, the aforementioned conductive polymer film can be used, for example, as a solid electrolyte or transparent electrode in a capacitor.
[0107] In other words, the conductive polymer film is characterized by containing a polythiophene (A) and a carbon material (B) which include at least one structural unit selected from the group consisting of the structural unit represented by the general formula (1) and the structural unit represented by the general formula (2), and may also contain components which the conductive polymer composition may contain.
[0108] In the conductive polymer film described above, the composition ratio of the polythiophene (A) to the carbon material (B) is preferably 0.001 to 5 parts by weight of the carbon material (B) per 1 part by weight of the polythiophene (A). [Examples]
[0109] Examples relating to the present invention are shown below.
[0110] The analytical instruments and measurement methods used in this embodiment are listed below. [GC measurement] Equipment: Shimadzu GC-2014 [NMR measurement] Equipment: VARIAN Gemini-200 [Surface resistance measurement] Equipment: Mitsubishi Chemical Corporation's Loresta GP MCP-T600 or Mitsubishi Chemical Corporation's Hiresta UX MCP-HT8000 [Film thickness measurement] Equipment: DEKTAK XT manufactured by BRUKER. [Viscosity measurement] Complete Viscometer / BROOKFIELD VISCOMETER DV-1 Prime [Particle size measurement] Equipment: Microtrac Nanotrac UPA-UT151, manufactured by Nikkiso Co., Ltd. [Electrical conductivity measurement of self-doped conductive polymers] A 0.5 ml solution containing a self-doped conductive polymer was cast onto a 25 mm square alkali-free glass plate treated with UV ozone, dried on a hot plate at 60°C for 30 minutes, and then heated at 200°C for 30 minutes to obtain a conductive polymer film. The obtained conductive polymer film was subjected to the surface resistance measurement and film thickness measurement described above. The conductivity was calculated from the surface resistance and film thickness based on the following formula. [conductivity] Conductivity [S / cm]=10 4 (Surface resistance [Ω / □] × Film thickness [μm]) [Method for manufacturing radio wave absorbing material] The conductive polymer composition prepared in the example was applied to a polyester film (Cosmoshine A4100, manufactured by Toyobo) using a wire bar coater to form a coating with a wet film thickness of 100 μm. Then, it was heated and dried in air at 120°C for 5 minutes to obtain an electromagnetic wave absorbing material. [Radio wave shielding measurement] Measurements were performed using the free-space method with a KEYCOM DPS10 and an Anritsu ME7838A at 26.5GHz to 40GHz. [Method for manufacturing conductive films] The conductive polymer composition prepared in the example was applied to a 500 mm square alkali-free glass plate using a wire bar coater to form a coating with a wet film thickness of 100 μm. Then, it was heated and dried in air at 120°C for 5 minutes to obtain a conductive film.
[0111] Synthesis Example 1. Synthesis of 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-methyl-1-propanesulfonate sodium [a compound represented by formula (6) below]. Under a nitrogen atmosphere, 0.437 g (10.9 mmol) of 60% sodium hydride and 37 ml of toluene were charged into a 100 ml round-bottom flask, and then 1.52 g (8.84 ml) of (2,3-dihydrothieno[3,4-b][1,4]dioxin-2-yl)methanol was added. The reaction mixture was then heated to reflux temperature and stirred at that temperature for 1 hour. Subsequently, a mixture of 1.21 g (8.89 mmol) of 2,4-butanesultone and 10 ml of toluene was added dropwise, and the mixture was stirred at the same temperature for 2 hours. After cooling, the resulting reaction mixture was added dropwise to 160 ml of acetone and reprecipitation was performed. The obtained powder was filtered and vacuum-dried to obtain 1.82 g of pale yellow powder in yield of 62%. NMR measurements confirmed that this is sodium 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-methyl-1-propanesulfonate, represented by the following formula (6).
[0112] [ka]
[0113] 1 H-NMR(D2O)δ(ppm);6.67(s,2H),4.54-4.60(m,1H),4.45(dd,1H,J=12.0,2.2Hz),4.26(dd,1H,J=12 .0,6.8Hz),3.90-3.81(m,4H),3.10-3.18(m,1H),2.30-2.47(m,1H),1.77-1.92(m,1H),1.45(d,3H) 13 C-NMR(D2O)δ(ppm);14.91,31.22,53.13,66.18,69.18,73.29,73.36,100.81,100.94,140.88,141.06 Synthesis example 2. Synthesis of polythiophene (A) [polymers containing structural units represented by formula (7) or formula (8) below]. In a 500 ml separable flask, 10 g (30 mmol) of 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-methyl-1-propanesulfonate sodium, synthesized according to Synthesis Example 1, and 150 g of water were added. After dissolution, 2.94 g (18.1 mmol) of anhydrous iron(III) chloride was added at room temperature and the mixture was stirred for 20 minutes. Then, a mixed solution consisting of 14.5 g (60.4 mmol) of sodium persulfate and 100 g of water was added dropwise while maintaining the reaction mixture temperature below 30°C. After stirring at room temperature for 3 hours, the reaction mixture was added dropwise to 800 g of acetone to precipitate a black Na-type polymer. By filtering and vacuum-drying the polymer, 18.0 g of crude polymer of 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-methyl-1-propanesulfonate sodium was obtained.
[0114] Next, 700 g of a 2 wt% solution prepared by adding water to 14.5 g of the crude polymer was passed through a column packed with 200 ml of Lewatit MonoPlus S100 (H-type) cation exchange resin (space velocity = 1.1) to obtain 738 g of the H-type polymer solution. Furthermore, this polymer solution was purified by cross-flow ultrafiltration (filter = Vivaflow 200, molecular weight cutoff = 5,000, transmission ratio = 5) to obtain 698 g of a deep ultramarine solution of a polymer (polythiophene (A)) consisting of structural units represented by formula (7) or formula (8) below. The amount of polythiophene (A) contained in this polymer solution was 0.74 wt%. In addition, it contained iron ions and sodium ions at 44 ppm and 12 ppm (relative to the polymer), respectively.
[0115] [ka]
[0116] [ka]
[0117] Synthesis example 3. A methanol solution of dioctylamine was added to an aqueous solution of polythiophene (A) obtained in Synthesis Example 2, and the mixture was stirred to obtain composition (C) of polythiophene (A) and dioctylamine. Subsequently, water and methanol were removed by vacuum filtration to obtain a solid, which is the composition of polythiophene (A) and dioctylamine. 1 g of the solid was mixed and stirred with 99 g of 2-propanol to obtain a polythiophene (A) IPA solution.
[0118] Example 1. To prepare 5.00 g of an aqueous solution containing 1.2 wt% polythiophene (A) consisting of structural units represented by formula (7) or formula (8) above, which was prepared by adjusting the concentration of the concentrated ultramarine solution (0.74 wt% polythiophene (A) aqueous solution) obtained in Synthesis Example 2, 1.00 g of a single-walled carbon nanotube aqueous dispersion (0.2 wt% solid content aqueous dispersion, single-walled carbon nanotube diameter 1-3 nm) manufactured by Meijo Nanocarbon as carbon material (B), and 14.0 g of water were added. The mixture was stirred at a mixing temperature of 25°C for 1 hour to obtain a conductive polymer composition with a solid content of 0.31 wt%. Using this conductive polymer composition, a conductive polymer film was prepared using the method described in [Measurement of Conductivity of Self-Doped Conductive Polymers] above, and its conductivity was measured. The results are shown in Table 1.
[0119] Example 2. In Example 1, a conductive polymer composition and a conductive polymer film were obtained and evaluated according to the method of Example 1, except that 5.00 g of an aqueous solution containing 1.2% by weight of polythiophene (A), 3.00 g of Meijo Nanocarbon's single-walled carbon nanotube aqueous dispersion EC-DH (solid content concentration 0.2% by weight, single-walled carbon nanotube diameter 1-3 nm) was used as the carbon material (B), and 12.0 g of water was used. The results are shown in Table 1.
[0120] Example 3. In Example 1, a conductive polymer composition and a conductive polymer film were obtained and evaluated according to the method of Example 1, except that 5.00 g of an aqueous solution containing 1.2% by weight of polythiophene (A), 9.00 g of Meijo Nanocarbon's single-walled carbon nanotube aqueous dispersion EC-DH (solid content concentration 0.2% by weight, single-walled carbon nanotube diameter 1-3 nm) was used as the carbon material (B), and 6.00 g of water was used. The results are shown in Table 1.
[0121] Example 4. In Example 1, a conductive polymer composition and a conductive polymer film were obtained and evaluated according to the method of Example 1, except that 5.00 g of an aqueous solution containing 1.2% by weight of polythiophene (A) was used, and 15.0 g of Meijo Nanocarbon's single-walled carbon nanotube aqueous dispersion EC-DH (aqueous dispersion with a solid content of 0.2% by weight, and the diameter of the single-walled carbon nanotubes is 1-3 nm) was used as the carbon material (B). The results are shown in Table 1.
[0122] Example 5. In Example 2, a conductive polymer composition and a conductive polymer film were obtained and evaluated according to the method of Example 2, except that the mixing temperature was changed to 60°C. The results are shown in Table 1.
[0123] Comparative Example 1. A concentrated ultramarine solution (a 0.74 wt% polythiophene(A) aqueous solution) obtained in Synthesis Example 2 was prepared by adjusting the concentration of an aqueous solution containing 1.2 wt% polythiophene(A) consisting of structural units represented by formula (7) or formula (8) above. 5.00 g of this aqueous solution was mixed with 15.0 g of water and stirred at a mixing temperature of 25°C for 1 hour to obtain a conductive polymer aqueous solution with a solid content of 0.30 wt%. 0.5 ml of this conductive polymer aqueous solution was cast onto a 25 mm square alkali-free glass plate treated with UV ozone, dried on a hot plate at 60°C for 30 minutes, and then heated at 200°C for 30 minutes to obtain a conductive film. The evaluation results of the obtained conductive film are shown in Table 2.
[0124] Comparative Example 2. As carbon material (B), 0.5 ml of Meijo Nanocarbon's single-walled carbon nanotube aqueous dispersion EC-DH (aqueous dispersion with a solid content of 0.2 wt%, and single-walled carbon nanotube diameters of 1-3 nm) was cast onto a 25 mm square alkali-free glass plate treated with UV ozone. The plate was dried on a hot plate at 60°C for 30 minutes, and then heated at 200°C for 30 minutes to obtain a conductive film. The evaluation results of the obtained conductive film are shown in Table 2.
[0125] Comparative Example 3. 5.44 g of PEDOT:PSS aqueous dispersion (aqueous dispersion with a solid content of 1.1% by weight) was mixed with 1.00 g of ethylene glycol and 13.56 g of water, and stirred at a mixing temperature of 25°C for 1 hour to obtain a conductive composition with a solid content of 0.30% by weight. 0.5 ml of this conductive composition was cast onto a 25 mm square alkali-free glass plate that had been treated with UV ozone, dried on a hot plate at 60°C for 30 minutes, and then heated at 200°C for 30 minutes to obtain a conductive film. The evaluation results of the obtained conductive film are shown in Table 2.
[0126] Comparative Example 4. To 5.44 g of PEDOT:PSS aqueous dispersion (aqueous dispersion with a solid content of 1.1 wt%), 3.00 g of Meijo Nanocarbon's single-walled carbon nanotube aqueous dispersion EC-DH (aqueous dispersion with a solid content of 0.2 wt%), 1.00 g of ethylene glycol, and 10.56 g of water were added as carbon material (B). The mixture was stirred at a mixing temperature of 25°C for 1 hour to obtain a conductive composition with a solid content of 0.33 wt%. 0.5 ml of this conductive composition was cast onto a 25 mm square alkali-free glass plate treated with UV ozone, dried on a hot plate at 60°C for 30 minutes, and then heated at 200°C for 30 minutes to obtain a conductive film. The evaluation results of the obtained conductive film are shown in Table 2.
[0127] [Table 1]
[0128] [Table 2]
[0129] As shown in Tables 1 and 2, while the conductivity hardly improved when combining the conventionally known conductive polymer PEDOT:PSS with a carbon material (595 S / cm → 655 S / cm), a significant improvement in conductivity was observed when the conductive polymer of the present invention was combined with a carbon material (642 S / cm → approximately 900 S / cm). This remarkable improvement in conductivity is based on the unique action of the conductive polymer of the present invention and exhibits an unprecedented and unique effect.
[0130] Example 6. To prepare a concentrated ultramarine solution (a 0.74 wt% polythiophene (A) aqueous solution) obtained in Synthesis Example 2, 3.60 g of an aqueous solution containing 2.8 wt% polythiophene (A) consisting of structural units represented by formula (7) or formula (8) above was prepared by adjusting the concentration. To this aqueous solution, 5.00 g of Meijo Nanocarbon's single-walled carbon nanotube aqueous dispersion EC-DH (a 0.2 wt% solid content aqueous dispersion, single-walled carbon nanotube diameter 1-3 nm) and 1.40 g of water were added as carbon material (B). The mixture was stirred and mixed at a mixing temperature of 25°C for 1 hour to obtain a conductive polymer composition with a solid content of 1.1 wt%. The radio wave absorbing material was prepared using the method described in [Method for Preparing Radio Wave Absorbing Material] above, and its radio wave absorption performance was measured. The maximum radio wave shielding characteristics in the 26.5-40 GHz range are shown in Table 3.
[0131] Example 7. In Example 6, the same procedure as in Example 6 was performed, except that 5.00 g of Meijo Nanocarbon's single-walled carbon nanotube aqueous dispersion EC-DH was changed to 6.00 g, and 1.40 g of water was changed to 0.4 g, to obtain a conductive polymer composition with a solid content concentration of 1.12% by weight. The radio wave absorbing material was prepared using the method described in [Method for Preparing Radio Wave Absorbing Material] above, and its radio wave absorption performance was measured. The maximum radio wave shielding characteristics in the 26.5 to 40 GHz range are shown in Table 3.
[0132] Example 8. In Example 6, the same procedure as in Example 6 was performed, except that 5.00 g of Meijo Nanocarbon's single-walled carbon nanotube aqueous dispersion EC-DH was changed to 1.00 g, and 1.40 g of water was changed to 5.4 g, to obtain a conductive polymer composition with a solid content concentration of 1.01% by weight. The radio wave absorbing material was prepared using the method described in [Method for preparing radio wave absorbing material] above, and its radio wave absorption performance was measured. The maximum radio wave shielding characteristics in the 26.5 to 40 GHz range are shown in Table 3.
[0133] Reference example 1 A radio wave absorbing material was prepared using 10.00 g of a conductive polymer aqueous solution containing 1.0 wt% polythiophene(A) consisting of structural units represented by formula (7) or formula (8) above, which was prepared by adjusting the concentration of the concentrated ultramarine solution (0.74 wt% polythiophene(A) aqueous solution) obtained in Synthesis Example 2. The radio wave absorbing performance was measured using the method described in [Method for Preparing Radio Wave Absorbing Materials] above. The maximum radio wave shielding characteristics in the 26.5~40 GHz range are shown in Table 3.
[0134] Reference example 2 As carbon material (B), 5.00 g of Meijo Nanocarbon's single-walled carbon nanotube aqueous dispersion EC-DH (aqueous dispersion with a solid content of 0.2 wt%, and the diameter of the single-walled carbon nanotubes is 1-3 nm) was mixed with 5.00 g of water, and the mixture was stirred at 25°C for 1 hour to obtain an aqueous dispersion of carbon nanotubes with a solid content of 0.1 wt%. The radio wave absorbing material was prepared using the method described in [Method for Preparing Radio Wave Absorbing Material] above, and its radio wave absorption performance was measured. The maximum radio wave shielding characteristics in the 26.5-40 GHz range are shown in Table 3.
[0135] [Table 3]
[0136] As shown in Table 3, the composition of the present invention, which includes a polythiophene (A) containing a structural unit represented by formula (7) or formula (8) and a carbon material (B), exhibits the effect of providing excellent radio wave shielding properties that cannot be obtained by (A) or (B) alone.
[0137] Example 9. To 0.1 g of a 1.00 wt% polythiophene (A) IPA solution obtained in Synthesis Example 3, 9.9 g of SIGMA-Aldrich 792462 single-walled carbon nanotube / alcohol solution (a solid content alcohol dispersion with a solid content of 0.13 wt%) was added as carbon material (B). The mixture was stirred at a mixing temperature of 25°C for 1 hour to obtain 10 g of a conductive polymer composition with a solid content of 0.14 wt%. Using this conductive polymer composition, a conductive film was prepared using the method described in [Method for Preparing Conductive Films] above, and its conductivity was measured. The conductivity is shown in Table 4.
[0138] Example 10. To 0.5 g of a 1.00 wt% polythiophene (A) IPA solution obtained in Synthesis Example 3, 9.5 g of SIGMA-Aldrich 792462 single-walled carbon nanotube / alcohol solution (a solid content alcohol dispersion with a solid content of 0.13 wt%) was added as carbon material (B). The mixture was stirred at a mixing temperature of 25°C for 1 hour to obtain 10 g of a conductive polymer composition with a solid content of 0.17 wt%. Using this conductive polymer composition, a conductive film was prepared using the method described in [Method for Preparing Conductive Films] above, and its conductivity was measured. The conductivity is shown in Table 4.
[0139] Reference example 3 A 1.00 wt% polythiophene(A)IPA solution obtained in Synthesis Example 3 was used to prepare a conductive film using the conductive polymer composition and the method described in [Method for Preparing Conductive Films] above. The conductivity was then measured. The conductivity is shown in Table 4.
[0140] Reference example 4 As carbon material (B), a SIGMA-Aldrich 792462 single-walled carbon nanotube / alcohol solution (alcohol dispersion with a solid content of 0.13% by weight) was used as the conductive polymer composition, and a conductive film was prepared using the method described in [Method for Preparing Conductive Films] above, and its conductivity was measured. The conductivity is shown in Table 4.
[0141] [Table 4]
[0142] As shown in Table 4, the composition of the present invention, which includes polythiophene (A), carbon material (B), and compound (C), exhibits the effect of providing excellent conductivity that cannot be obtained by (A) or (B) alone. [Industrial applicability]
[0143] The polythiophene of the present invention has higher conductivity than conventional materials (for example, Patent Documents 1 and 2), making it suitable for use as an antistatic agent, a solid electrolyte for capacitors, an antistatic film, and a separator for wound aluminum electrolytic capacitors. Furthermore, it is expected to have applications in electrochromic elements, transparent electrodes, transparent conductive films, thermoelectric conversion materials, chemical sensors, actuators, electromagnetic shielding materials, and the like.
Claims
1. A polythiophene (A) containing at least two structural units selected from the group consisting of structural units represented by the following general formula (1) and structural units represented by the following general formula (2), a carbon material (B), and a compound (C) capable of forming an ion pair with the sulfonic acid group of the polythiophene (A) are contained in one or more solvents (D) selected from the group consisting of organic solvents and water. A conductive polymer composition comprising 0.001 to 10% by weight of the polythiophene (A) and 0.001 to 5% by weight of the carbon material (B). 【Chemistry 1】 [In the above general formulas (1) and (2), R 2 [where m represents a hydrogen atom, a methyl group, an ethyl group, a linear or branched alkyl group having 3 to 6 carbon atoms, or a fluorine atom; where m represents an integer from 1 to 10; and where n represents 0 or 1.]
2. The conductive polymer composition according to claim 1, wherein the compound (C) is 0.001 to 20% by weight.
3. A polythiophene (A) containing at least two structural units selected from the group consisting of structural units represented by the following general formula (1) and structural units represented by the following general formula (2), a carbon material (B), and one or more additives (E) selected from the group consisting of water-soluble resins and surfactants, are contained in one or more solvents (D) selected from the group consisting of organic solvents and water. A conductive polymer composition comprising 0.001 to 10% by weight of the polythiophene (A) and 0.001 to 5% by weight of the carbon material (B). 【Chemistry 2】 [In the above general formulas (1) and (2), R 2 [where m represents a hydrogen atom, a methyl group, an ethyl group, a linear or branched alkyl group having 3 to 6 carbon atoms, or a fluorine atom; where m represents an integer from 1 to 10; and where n represents 0 or 1.]
4. The conductive polymer composition according to claim 3, wherein the additive (E) is 0.001 to 20% by weight.
5. The present invention comprises a polythiophene (A) containing at least one structural unit selected from the group consisting of structural units represented by the following general formula (1) and structural units represented by the following general formula (2), and a carbon material (B), and further comprises one or more additives (E) selected from the group consisting of a compound (C) capable of forming an ion pair with the sulfonic acid group of the polythiophene (A), or water-soluble resins and surfactants. A conductive polymer film in which the composition ratio of the polythiophene (A) and the carbon material (B) is 0.001 to 5 parts by weight of the carbon material (B) per 1 part by weight of the polythiophene (A). 【Transformation 3】 [In the above general formulas (1) and (2), R 2 [where m represents a hydrogen atom, a methyl group, an ethyl group, a linear or branched alkyl group having 3 to 6 carbon atoms, or a fluorine atom; where m represents an integer from 1 to 10; and where n represents 0 or 1.]
6. The conductive polymer film according to claim 5, which is a coated and dried film of the conductive polymer composition according to any one of claims 1 to 4.
Citation Information
Patent Citations
Aqueous conductive polymer solution and conductive polymer film
JP2015063652A
Conductive polymer aqueous solution and conductive polymer film
JP2015147834A